ELIMINATING CONCURRENCY BUGS WITH CONTROL ENGINEERING. - Kelly, Terence; Yin Wang; Lafortune, Stéphane; Mahlke, Scott (Computer (00189162), 2009)
The article discusses the elimination of concurrency bugs through controlled computer engineering. Concurrency problems are linked with parallel programming and they found that the challenges can be solved through control engineering based on classical control theory. The Gadara software used is designed to enable multithreaded programs to avoid deadlocks.